Stability and periphery in Graphic design: دينا محمد عناد (Al-Academy, 2016)
Graphic design art depends on changeable cognitive systems which their relation and items relying on the accumulation of humane knowledge and thong and the humane look to the venality and his explanation to the relation between him and the venality , then the graphic design art becomes an important item of this accumulation knowledge besides , it is on kind of knowledge kinds . The technological advancement in communication lauds to increasing in communication media and design methods , where the computer and its application in graphic design promotes the design process because of it's capalebities which lead to in creasing in production process , minimizing the cost and time and achieving creative and aesthetic aspect because of it's feat Wes in art program and it's technique in designer . This study which title (Stability and periphery in Graphic design ) sheds the light on this knowledge to understand this subject deeply through three chapters : first one about the problem of the study, the 2nd about the theoretical and previous studies which consists of three axes: The 1st on (The stability and periphery concept in art) , the 2nd on ( the stability and periphery in the structure of graphic item), and the 3rd on (the stability and periphery according to the modern techniques). Third chapter consists of the results of this paper and the scientific suggestions by the researcher which are as following : 1- The periphery in the Stability of graphic design is because it's direct connection in humane needs and the changing of scientific culture due to the age and culture changes . where the stability is stewing from experience , the designer depends on, while the periphery is building and using agents according new system and program. 2- The graphic peripheries connect to changing humane needs as those like functional and living ones which are basically changeable because of time and place. 3- The total periphery in design structure is the result of scientific advancement and productions technology leading to the emergence of electronic art creator and the application of digital technology in design press fields. As for stabilities, they are concepts and contents aiming by the design process which aims at achieving the goal which is attracting the attention of the receiver through every new and creative design.